PENGARUH PENERAPAN METODE CUL-DE-SAC (NOSE PINCHING) TERHADAP KLIEN DISGLOSIA: Effects of the Application of CUL-DE-SAC (Nose Pinching) Method on Dysglossia Clients. - Riani Shopianty (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Politeknik Al Islam Bandung, 2021)
A speech disorder that occurs due to deformities of speech organs, especially articulators, is called dysglosia. The congenital deformities of speech organs of people around us result in various difficulties in communicating due to inaccuracies or inconsistencies in articulating words. One of the methods in the field of speech therapy being able to to overcome the problems including the abnormalities in sound resonance is Cul-de-sac (Nose Pinching) method. This study aimed to determine the effect of the application of the Cul-de-sac (Nose Pinching) method in increasing the awareness of Dysglosia clients about the differences in sound resonance in the nasal cavity and oral cavity when producing consonants and reducing nasal air emissions when producing consonant sibilant apicoalveolar / s. / at the Cleft Center Bandung. The research method used is single subject experiment. Data were collected through interviews with the client's parents, direct observation of the client, tests, and a document study of the client's medical record. After 15 sessions of therapy using the method, the client's ability had improved for about 65% and he was successfully able to pronounce the consonant of / s / in the presence of a nasal air emission between 1-2 cm. Therefore, based on the results it can be concluded that the Cul-de-sac (Nose Pinching) method has influenced as much as 65% of nasal air emission reduction.